A Near Room Temperature Curie Temperature in a New Type of Diluted Magnetic Semiconductor (Ba,K)(Zn,Mn)2As2 - Yi Peng; Xiang Li; Luchuan Shi; Guoqiang Zhao; Jun Zhang; Jianfa Zhao; Xiancheng Wang; Bo Gu; Zheng Deng; Yasutomo J. Uemura; Changqing Jin (Advanced Physics Research)
Abstract Achieving room‐temperature ferromagnetism is one of the major challenges for diluted magnetic semiconductors (DMS). (Ba,K)(Zn,Mn)2As2 (BZA) belongs to a new type of DMS materials that feature independent spin and carrier doping. In previous studies, BZA shows a reliable Curie temperature (TC) of 230 K, a record among these types of materials. In this work, progress in further experimentally enhancing TC of BZA to 260 K is reported by increasing Mn concentration with parallel K doping, as supported by complementary first‐principles calculations. A sufficient carrier concentration can suppress the short‐range antiferromagnetic interaction of the nearest Mn─Mn pair, which suppresses ferromagnetism in DMS materials. Consequently, a higher TC has been obtained in BZA with improved Mn‐ and K‐doping levels by using high‐pressure synthesis that effectively eliminates structural distortion and overcomes the limitation of chemical solution in BZA. The work demonstrates an effective strategy to enhance TC in DMS systems.